The Image of Great Britain in the Soviet Press in the Context of the Spanish Civil War (1936‒1939) - S. M. Lunev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The developments of the Spanish Civil War in 1936–1939, including its international aspects, have been thoroughly studied both in foreign and in Russian historiography. However, the introduction of new research approaches, in this case imagology, allows us to revisit even the well-established views. The paper examines the сreation and subsequent development of the image of Great Britain in the Soviet press in the context of the Spanish Civil War. The research draws on publications in the Soviet ‘Pravda’ and ‘Izvestiya’ newspapers, as well as in the ‘Ogoniok’, ‘Za rubezhom’ and ‘Agitator’s Sputnik’ magazines. The study reveales a rather ambiguous position of the Soviet press in relation to the British policy in Spain. Several topics played a key role in creating the image of the ‘Foggy Albion’ in the Soviet press. The leitmotif of publications of the Soviet journalists was the image of the empire in decline. In this regard, the Soviet press emphasized the acquiescence of the British government faced with aggressive actions from Francoists backed by Germany and Italy, as well as its inability to protect national interests of its own state. Parallel to this, the image of Great Britain as a split society was created. The Soviet journalists stressed that passivity of the government caused mounting criticism from both political left and right. At the same time, they praised the work of the civil society and volunteers in support of the republic. Finally, the Soviet media bashed London for its gradual drift from non-intervention towards appeasement and even direct inducement of aggressors. The author concludes that the image of Great Britain created in the Soviet press was intended to convince the Soviet public opinion in the fallacy of the British policy. In the face of an impending global war, London was portrayed as an unreliable ally, prone to concessions to aggressors.